MONITORING OF BUSINESS ACTIVITIES OF RETAIL ENTERPRISES - Toshpulatov, Bobur (THE INNOVATION ECONOMY, 2026)
the article analyzes the theoretical and practical aspects of monitoring the business activities of retail enterprises. The study examines indicators for assessing the financial and economic performance of retail companies, mechanisms for forming a monitoring system, and ways to improve management efficiency through digital technologies. In addition, directions for cost optimization, increasing profit and profitability, and ensuring sustainable development of retail enterprises based on monitoring results are substantiated.